BEYOND GUIDANCE: THE MEDIATING ROLE OF CAREER ADAPTABILITY IN LINKING PERCEIVED MENTORING TO WORK READINESS AMONG INDONESIAN GEN Z STUDENTS - Chrysan Gomargana; Kevin Aprilio Wibowo (Faculty of Psychology, Diponegoro University, 2025)
In Indonesia’s dynamic employment landscape, Generation Z faces considerable challenges in transitioning from university to the workforce. Despite national initiatives to enhance employability, many graduates still feel underprepared for early career demands. Guided by career construction and mentoring theory, this study examines how perceived mentoring functions shape career adaptability and work readiness among final-year university students who have had mentors since their freshman year. A mediation model was proposed in which career adaptability—defined by the self-regulatory capacities of concern, control, curiosity, and confidence—serves as the mechanism linking mentoring to work readiness. Data were collected from 200 students (M = 21.1, SD = 0.6) using standardized questionnaires on perceived mentoring, career adaptability, and work readiness. Structural equation modeling showed that perceived mentoring significantly predicted career adaptability (β = .61, p < .001) and work readiness (β = .27, p < .01), while career adaptability strongly predicted work readiness (β = .64, p < .001). Bootstrapped mediation analysis confirmed a significant indirect effect, supporting partial mediation. These findings underscore the importance of sustained mentoring and adaptive capacities in preparing youth for uncertain labor markets, while extending mentoring theory to collectivist, non-Western contexts and offering practical implications for educators and policymakers.